Effect of Lambda-Cyhalothrin on Nutritive Content of Edible Muscle - Suman Gulati; Arul Suyambunathan; K. Revathi; E. Logeswari; R. Latha (The Bioscan, 2025)
Fish are a significant group of organisms and a significant source of food that is high in protein for human consumption. Many different types of toxicants can affect fish. Fish development and nutritional value are changed by pesticides. Fish and other aquatic invertebrates are extremely poisoned by the synthetic pyrethroid lambda-cyhalothrin. According to its nutritional profile, catfish is a very healthy and wholesome food that is high in protein, low in fat and cholesterol, and a good source of several vitamins and minerals. The purpose of this study is to investigate how lambda-cyhalothrin affects the nutritional value of edible muscle. Through proximate, mineral, and vitamin analysis, the nutritional value of edible muscle was investigated. A notable decrease (P < 0.05) was observed in the lipid, protein, and carbohydrate levels exposed to the two different sub-lethal concentrations of the pyrethroid. Different vitamins of the edible muscle of freshwater catfish exposed to lambda showed a decline after 45 days of exposure to the pyrethroid. The composition of various minerals of the edible muscle also showed a decline after 45 days of exposure to the pyrethroid.